A Parametric View of Hubble Parameter for Scalar Field Dark Energy Model - Goswami, Sangita; Das, Sudipta (Current Indian Science, 2023)
Purpose of the study In our present work, we have considered a simple parametric form of the Hubble parameter (H) for a canonical scalar field model described within a spatially flat FRW spacetime framework. Here we have considered a well-behaved parametrization scheme of the normalized Hubble parameter to explain the expansion history of the universe. Methods Under this scenario, we have obtained the analytic solutions for various relevant cosmological parameters. We have also reconstructed the potential function V(φ) for the scalar field φ. Results It has been found that the deceleration parameter (q) shows exactly the nature which is well expected, i.e., an accelerated expansion for low z limit and deceleration for high z limit, which is essential for the structure formation of the Universe. Detailed data analysis has been carried out to check the viability of the proposed theoretical model by using combined dataset SNIa+H(z)+BAO/CMB and put constraints on the cosmological parameters, viz. the present value of the Hubble parameter H0. Conclusion As it has been observed that the deceleration parameter undergoes a smooth transition from an accelerating phase to decelerating expansion, this result supports the structure formation at the early time and the late time cosmic acceleration measurements. The results are found to be closer to the value obtained by the PLANCK collaboration.
Keywords: Parametrization